Experimental studies of the interaction of ion- and plasma-streams with carbon-based targets placed near a cathode of plasma-focus facility - Gribkov, V.A.; Dubrovsky, A.V.; Miklaszewski, R.; Paduch, M.; Tomaszewski, K.; Scholz, M.; Pimenov, V.N.; Ugaste, Yu.E.; Sadowski, M.J.; Skladnik-Sadowska, E.; Szydlowski, A.; Malinowski, K.; et al. (Вопросы атомной науки и техники, 2005)
The paper presents measuring techniques and results of experiments performed within the PF-1000 PlasmaFocus facility in order to investigate the interaction of high-energy deuteron beams (of ED >100 keV) and deuterium plasma streams (of vstr ≥ 10⁷ cm/s) with carbon-based materials, designed for the first wall of a future thermonuclear reactor of the ICF or MCF type. Particular attention was paid to the verification of diagnostic techniques, which might be used for time- and space-resolved studies of the interaction of ion- and plasmastreams with the targets placed near the cathode outlet inside the experimental device. У роботі описані вимірювальна техніка і результати експериментів, проведених на плазмовому фокусі PF-1000, спрямованих на вивчення взаємодії высокоенергетичних пучків дейтронів (ED >100 кэВ) і потоків водневої плазми (vstr ≥ 10⁷ см/с) з матеріалами на основі вуглецю, розробленими для використання в ролі першої стінки майбутнього термоядерного реактора на основі інерціального або магнітного утримання. Особлива увага була приділена перевірці працездатності діагностичного устаткування, використовуваного для дослідження з тимчасовим і просторовим дозволом взаємодії іонних і плазмових потоків з мішенями, розташованими поблизу торця катода експериментальної установки. В работе описаны измерительная техника и результаты экспериментов, проведенных на плазменном фокусе PF- 1000, направленных на изучение взаимодействия высокоэнергетичных пучков дейтронов (ED >100 кэВ) и потоков водородной плазмы (vstr ≥ 10⁷ cм/с) с материалами на основе углерода, разработанными для использования в качестве первой стенки будущего термоядерного реактора, на основе инерциального или магнитного удержания. Особое внимание было уделено проверке работоспособности диагностического оборудования, используемого для исследования с временным и пространственным разрешением взаимодействия ионных и плазменных потоков с мишенями, расположенными вблизи торца катода экспериментальной установки.